2022
DOI: 10.54037/wjps.2022.100309
|View full text |Cite
|
Sign up to set email alerts
|

Analytical method development and validation for simultaneous estimation of meropenem and vaborbactam in bulk and pharmaceutical dosage form by RP-HPLC

Abstract: A simple, specific and accurate reverse phase high performance liquid chromatographic method was developed for the simultaneous determination Meropenemand Vaborbactaminpharmaceutical dosage form. The column used was KromosilC18(150mm x 4.6 mm, 5m)in isocratic mode, with mobile phase containing phosphatebufferandacetonitrile (45:55v/v). The buffer is prepared by adding accurately weighed 1.36gm of PotassiumdihyrogenOrtho phosphate in a 1000ml of Volumetric flask add about 900ml o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Single-charge positive ion mass transitions were selected for optimal sensitivity and specificity by analyzing the MS/MS fragmentation pattern spectra of analytes (data not shown) and by reviewing the literature [ 17 , 18 , 19 ]. Proton ion adducts of MRP and meropenem-d6 (MRP-d6) were detected by means of the following mass transitions: 384.2–141.0 m / z and 390.2–147.1 m / z and daughter ion intensity over retention time were used to generate multiple reaction monitoring (MRM) ion extraction chromatograms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single-charge positive ion mass transitions were selected for optimal sensitivity and specificity by analyzing the MS/MS fragmentation pattern spectra of analytes (data not shown) and by reviewing the literature [ 17 , 18 , 19 ]. Proton ion adducts of MRP and meropenem-d6 (MRP-d6) were detected by means of the following mass transitions: 384.2–141.0 m / z and 390.2–147.1 m / z and daughter ion intensity over retention time were used to generate multiple reaction monitoring (MRM) ion extraction chromatograms.…”
Section: Resultsmentioning
confidence: 99%
“…We are well aware that in LC-MS/MS methods isotopically labeled analogue should be used as the internal standard of the corresponding analyte, but this was unfeasible due to commercial unavailability at the time of the study. Consequently, we used AVI-C13 as IS, similar to what was previously done by other methods assessing MER/VBR plasma concentrations [ 17 , 18 , 19 ], with good results. Finally, the short stability of MRP, namely an issue very well-known in literature [ 17 , 20 ], was confirmed in the stability test conducted in our study, whereas VBR showed longer stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations